Observability, Social Proximity, and the Erosion of Norm Compliance - Cristina Bicchieri; Eugen Dimant; Simon Gaechter; Daniele Nosenzo (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study how an individual's compliance with social norms is inuenced by other actors' norm compliance. In a repeated non-strategic Take-or-Give donation experiment we show that giving is considered socially appropriate while taking is socially inappropriate. Observing norm violations erodes an individual's own norm compliance. We show that the erosion of norm compliance is led by a change in norm-related beliefs. This change has a major effect on individuals who initially obey the norm, driving them to non-compliance, whereas initially non-compliant individuals do not change their taking behavior. Erosion is halted when individuals have even minimal social proximity to those they observe: individuals now also pay attention to norm followers.
Keywords: C92; D64; D90; 330; norm compliance; social norms; social proximity